Migration for Business: A Case Study of Goa - P. S. Devi; P.K. Sudarsan (Vikalpa)
Goa is a popular destination for migrants from other states. However, according to Census 2011, migration for business comprises only 2.7% of all migration. Using Census data, this study seeks to identify the factors that determine business migration to Goa. It is found that while the size of population of the home state positively influences outmigration, distance has a dampening effect, though its importance as a deterrent is declining over time. The variables of literacy and GSDP do not exert much influence on the volume of migration. A field study conducted to gain insights into the experiences of the business migrant community in Goa shows that most of the respondents have a favourable opinion about Goa, with very few cases of discrimination and abuse.